0091 Enhancing the continuity of patient care using simulation: A pilot study investigating issues of hierarchy and communication amongst undergraduate healthcare students using high stakes, high fidelity simulation. (2nd November 2015) - Harper, Michael; Best, Darren; Robertson, Caroline
Abstract : Background: This presentation discusses data from a pilot study that investigated inter-professional 'high stakes' simulated patient care in the pre-hospital and peri-hospital environments and how issues of human factors such as communication and hierarchy influence patient care delivery and outcome. Methods: This was a pilot study with a single, convenient sample of undergraduate healthcare students. Sixty students met the inclusion criteria with 27 students consenting to participate. The design was to engage participants in a high fidelity simulation exercise where Paramedic students managed an acutely unwell patient in the pre-hospital setting aboard a simulation ambulance (Simbulance) before handing over to ODP students for onward transfer into a high fidelity simulation Emergency Department (ED) facility. The primary outcome was the identification of perceived responsibility for care of the patient and the influences on communication and handover of care. The secondary outcome was to elicit perceived learning and self-efficacy of participants. Data was collected through the analysis of any physiological changes to the manikin during transfer, video observation of participants and analysis of a post-simulation participant questionnaire. Results: Over half of the participants' handovers from the Simbulance to the transfer team there were delays in the perception and identification of who was responsible for the care of the patient. Often this delay affected the 'patient' negatively causing changes to the physiology (reduction in temperature/intermittent ventilation/delayed transfer). Conclusions: There are debates regarding the effectiveness of learning in simulation. 4 However, results from this pilot show that there is often a misguided perception of who is in 'charge' potentially due to a pre-disposed notion of hierarchy based on location. Future studies could investigate the development of human factor awareness in undergraduate learners as well as existing clinicians in order to potentially improve patient safety and clinical outcome. References: Rodger S, Webb G, Devitt L, Gilbert J, Wrightson G, McKeenen J. Clinical education and practice placements in the allied health professions: an international perspective. J Allied Health. 2008;37(1):53–62 Department of Health. A framework for technology enhanced learning . In: Health Do, ed. London, 2011 Birch L, Jones N, Doyle PM, Green P, McLaughlin A, Champney C, et al . Obstetric skills drills: evaluation of teaching methods. Nurse Educ Today. 2007;27(8): 915–22 Brindley PG, Dunn WF. Simulation for clinical research trials: a theoretical outline. J Crit Care 2009;24 (2):164–7. PubMed PMID: WOS:000266991700002